THE CORRELATION BETWEEN RISK FACTORS WITH INCIDENCE OF PREECLAMPSIA - Ammarie, Amalia Sumaya; Hani, Ummu; Do Toka, Wahyunita (Indonesian Journal for Health Sciences, 2024)
Preeclampsia is a disorder that occurs in the mother and fetus during pregnancy which is one of the problems in pregnancy worldwide, especially in countries with low maternal health levels. Many risk factors contribute to the incidence of preeclampsia, including age, obesity, gravida status or parity, anaemia, history of hypertension, previous history of preeclampsia, and multiple pregnancies. This study aims to determine the association of risk factors with the incidence of preeclampsia at RSUD Dr. H. Chasan Boesoirie Ternate. This is an observational-analytic study with 169 consecutive samples. Using the chi-square test there is a relationship between preeclampsia and age, obesity, and a history of hypertension (p0.001); anaemia (p=0.039). There is no relationship between preeclampsia and the status of gravida (p=0,514) and multiple pregnancies (p=0.525). It can be concluded that there is an association between preeclampsia and age, obesity, anaemia, and a history of hypertension and no association between preeclampsia and status of gravida and multiple pregnancies